Recruitment of GABA(A) Receptors in Chemoreceptor Pulmonary Neuroepithelial Bodies by Prenatal Nicotine Exposure in Monkey Lung - Fu, XW. (2009)
Pulmonary neuroepithelial bodies (NEB) act as airway oxygen sensors and produce serotonin, a variety of neuropeptides and are involved in autonomic nervous system control of breathing, especially during the neonatal period. We now report that NEB cells also express a GABAegic signaling loop that is increased by prenatal nicotine exposure. In this study, cultured monkey NEB cells show hypoxia-evoked spikes and hypoxia-sensitive K(+) current. As shown by both immunofluorescence and RT-PCR, monkey NEB cells synthesize and contain serotonin. The monkey NEB cells express the β2 and β3 GABA(A) receptor subunits, GAD and also express α7, α4 and β4 nicotinic receptor (nAChR) subunits. The α7 nAChR is co-expressed with GAD in NEB. The numbers of NEB and β3 GABA(A) receptor subunits expressed in NEB cells in lungs from control newborn monkeys were compared to lungs from animals that received nicotine during gestation. Prenatal nicotine exposure increased the numbers of NEB by 46% in lung and the numbers of NEB cells expressing GAD and GABA(A) β3 receptors increased by 67% and 66%, respectively. This study suggests that prenatal nicotine exposure can modulate NEB function by increasing the numbers of NEB cells and by increasing both GAD expression and β3 GABA(A) receptor subunit expression. The interaction of the intrinsic GABAergic system in the lung with nicotinic receptors in PNEC/NEB may provide a mechanism to explain the link between smoking during pregnancy and SIDS.